Analysis of histology-agnostic targets among soft tissue and bone sarcomas in the AACR GENIE database - Pestana, Roberto Carmagnani; Serrano, César (Frontiers in Oncology, 2023)
Background The development of novel therapies for patients with sarcoma is challenging due to the rarity and diversity of these mesenchymal neoplasms. Hence, histology-agnostic approvals can be of particular interest for the treatment of patients with soft tissue and bone sarcoma. Methods We queried the American Association for Cancer Research (AACR) Project Genomics Evidence Neoplasia Information Exchange (GENIE) database Cohort v12.0-Public to investigate the prevalence of currently Food and Drug Administration (FDA)-approved and other potentially actionable histology-agnostic alterations in patients with soft tissue and bone sarcoma. Targets were identified by a literature review by the authors. Results are presented for each cohort identified in the GENIE database, namely: (1) soft tissue sarcoma (STS), (2) gastrointestinal stromal tumor (GIST), (3) bone sarcoma, (4) uterine sarcoma, and (5) breast sarcoma. Results We identified 7,512 samples of 6,955 patients with sarcoma in the AAACR GENIE database v12.0-Public. Molecular alterations that could lead to the clinical use of a currently approved histology-agnostic therapy were identified in 2.1% of sarcomas (2.6% STS, 1.3% GIST, 1.4% bone, 2.7% uterine, and 0% breast). In addition, 2.9% of patients could be eligible for future histology-agnostic approvals. These specific mutations, fusions, and amplifications occurred in multiple histotypes in all cohorts. Discussion Exploring a public large-scale genomic database, we identified that 5% of patients with sarcoma could be eligible for current histology-agnostic FDA-approved drugs or future potential histology-agnostic indications. These actionable alterations were present in a wide variety of histologies in soft tissue and bone sarcomas, highlighting that next-generation sequencing can be considered for patients with advanced sarcoma to guide treatment strategies.